Study Guide for Statistics for Business and Financial Economics : A Supplement to the Textbook by Cheng-Few Lee, John C. Lee and Alice C. Lee - Moy, Ronald L.; Chen, Li-Shya; Kao, Lie Jane (Springer International Publishing : Imprint: Springer, 2015)
This Study Guide accompanies Statistics for Business and Financial Economics, 3rd Ed. (Springer, 2013), which is a business statistics textbook that uses finance, economics, and accounting data throughout the book. This Study Guide contains unique chapter reviews for each chapter in the textbook, formulas, examples, and additional exercises to enhance topics and their application. Solutions are included so students can evaluate their own understanding of the material. With more real-life data sets than the other books on the market, this study guide and the textbook that it accompanies, give readers all the tools they need to learn material in class and on their own. The topics covered are immediately applicable to facing uncertainty and the science of good decision making in financial analysis, econometrics, auditing, production, operations, and marketing research. Students in business degree programs will find this material particularly useful in their other courses and future work.